Tectonic movements and deformations within the Bishkek local GPS network (Northern Tien Shan) based on long-term space geodetic observations - @Kuzikov, Sergey I.; Prokhorov, Oleg A. (Геосистемы переходных зон)
The velocity field of modern crustal movements within the Bishkek local GPS network (the Northern Tien Shan) was studied for the years 1997–2021 of repeated space geodetic measurements. A regular decrease in the northern velocity component was shown from the southern block of Paleozoic rocks on the northern slope of the Kyrgyz Ala-Too Range through the middle block of Cenozoic formations and to the northern block of Quaternary deposits in the Chu Valley. Based on the velocity vectors, fields of different types of strain rates were constructed, which indicate a concentration of increased strain values up to 1.4‧10–7 /year within the middle Cenozoic block. Moreover, the high strain rate is not concentrated in fault zones and is dispersed over the area of the Cenozoic tectonic block, which is located at the junction of the northern spurs of the Kyrgyz Range and the Chu depression.